Theories of the Labor Movement, as Set Forth in Recent Literature - Cooper, Lyle W. (Quarterly Journal of Economics, 1928)
Journal Article Theories of the Labor Movement, as Set Forth in Recent Literature Get access Lyle W. Cooper Lyle W. Cooper Marquette University, Milwaukee Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 43, Issue 1, November 1928, Pages 154–170, https://doi.org/10.2307/1883945 Published: 01 November 1928